2000
DOI: 10.1111/j.1651-2227.2000.tb03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and growth velocity in obese children after very low calorie diet, exercise, and behavior modification

Abstract: The prevalence of obesity in American youth is increasing and treatment of the condition is difficult. We have developed a multi‐disciplinary weight reduction program that extends over 1 y and includes a very low‐calorie diet (VLCD) followed by a hypocaloric diet, exercise, and behavior modification. Based on data collected at baseline, at the end of the acute intervention phase (10–20 wk), and at 1‐y evaluation, we assessed the efficacy of this outpatient weight reduction program in treating obese children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The growth acceleration during the stay with the large weight loss was not expected. Some, mainly older studies, have reported a reduction in height velocity for children on weight‐reducing diets (38,39,40,41) while other results suggest that energy restrictions do not cause any negative effects on height as indicated in this study (19,27,29,30,42,43,44). A positive effect of weight reduction on height as observed in this study is rarely reported.…”
Section: Discussionsupporting
confidence: 50%
“…The growth acceleration during the stay with the large weight loss was not expected. Some, mainly older studies, have reported a reduction in height velocity for children on weight‐reducing diets (38,39,40,41) while other results suggest that energy restrictions do not cause any negative effects on height as indicated in this study (19,27,29,30,42,43,44). A positive effect of weight reduction on height as observed in this study is rarely reported.…”
Section: Discussionsupporting
confidence: 50%
“…This intensive programme featured medical supervision, medical nutrition therapy (hypocaloric diets), nutrition education, exercise therapy, activity education and behaviour modification. Earlier reports of this programme's success, carried out as an interventional study, had 100% of families participating in 10‐week and in 1‐year evaluations (31); subsequent reports stated that 33% of participants dropped out (most between 6 and 9 months) (32). There were no indicators of why these different outcomes were found; no analyses of differences between dropouts and completers were included.…”
Section: Attrition From Clinical Obesity Treatment Programmesmentioning
confidence: 99%
“…A few pilot studies have used protein-sparing modified fast, wherein carbohydrates are severely restricted but proteins are spared. It induces intense lipolysis and ketosis and hence, are not generally used in clinical practice in children and adolescents [29]. Physical activity is made more regular and tracked using logs or activity trackers.…”
Section: Level 3: Multidisciplinary Intensive Comprehensive and Structured Weight Loss Programmementioning
confidence: 99%